(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
In current investigation an attempt has been made to formulate and evaluate Quinapril mouth dissolving films using HPMC 50cps, E5, E15 and in combination of Pullulan by Solvent evaporation method. Sodium starch glycolate acts as a super disintegrating agent and it is shown that as the concentration of the super disintegrates increases the disintegration time decreases. The films were evaluated for weight variation, surface pH, folding endurance, drug content, dissolving time, disintegration time, and in-vitro dissolution studies. Based on the evaluation parameters F17 was to be optimized formulation. The optimized film (F17) showed the more drug release i.e 99.40 ± 5.30% within 7 min, lowest in vitro disintegration time 10 sec. FTIR studies proved no drug polymer interaction takes place. These results revealed that fast dissolving films of Quinapril could be formulated for quick onset of action which is required in the efficient management of hypertension.